Macular Hole Surgery: The Healing Process of Outer Retinal Layers to Visual Acuity Recovery. Issue 2 (March 2017) - Caprani, Simona M.; Donati, Simone; Bartalena, Luigi; Vinciguerra, Riccardo; Mariotti, Cesare; Testa, Francesco; Porta, Giovanni; Azzolini, Claudio
Purpose: To evaluate optical coherence tomography (OCT) modifications of outer retinal layers as determinants for functional recovery after surgery for idiopathic macular hole (IMH). Methods: This prospective study included 23 eyes of 23 consecutive patients who underwent vitreoretinal surgery for IMH. We excluded patients with other retinal diseases. Baseline and follow-up evaluations at months 3 and 6 included complete ophthalmologic and instrumental evaluations. Functional evaluation was performed by Best Corrected Visual Acuity (BCVA) and Amsler test. Morphologic evaluation was performed by spectral-domain 3D-OCT (Topcon, Tokyo, Japan) for a deep analysis of retinal layers as well as central retinal thickness evaluation. A standard 23-G or 25-G vitreoretinal surgery was performed, completed by posterior hyaloid and inner limiting membrane peeling by means of vital dyes and gas tamponade. Statistical analysis was performed on collected data. Results: The mean BCVA increased significantly from 0.57 ± 0.25 logMAR at baseline to 0.34 ± 0.22 logMAR at month 6. Intraretinal layers modification showed a progressive recomposition of inner segment/outer segment layer in 91% of patients at month 6. Retinal layers recomposition showed a progressive increase in all patients during follow-up from the immediate postoperative control to the last 6-month visit. Conclusions: Optical coherence tomography examination appears useful to investigate visual recovery after macular hole surgery. To ensure postsurgical functional increase, recomposition of all retinal layers, in particular in the outer retina, is mandatory. This process could be slow and not immediately observable during follow-up examinations.